Lời giải:
1. Với $x=36$ thì $\sqrt{x}=6$
Khi đó: $A=\frac{6-2}{6-1}=\frac{4}{5}$
2.
\(B=\frac{2x+1}{\sqrt{x}(\sqrt{x}-1)}+\frac{\sqrt{x}-1}{\sqrt{x}(\sqrt{x}-1)}-\frac{x}{\sqrt{x}(\sqrt{x}-1)}\)
\(=\frac{2x+1+\sqrt{x}-1-x}{\sqrt{x}(\sqrt{x}-1)}=\frac{x+\sqrt{x}}{\sqrt{x}(\sqrt{x}-1)}=\frac{\sqrt{x}(\sqrt{x}+1)}{\sqrt{x}(\sqrt{x}-1)}=\frac{\sqrt{x}+1}{\sqrt{x}-1}\)
3.
\(B:A=\frac{\sqrt{x}+1}{\sqrt{x}-1}.\frac{\sqrt{x}-1}{\sqrt{x}-2}=\frac{\sqrt{x}+1}{\sqrt{x}-2}=1+\frac{3}{\sqrt{x}-2}\)
Để $B:A$ nguyên thì $\sqrt{x}-2$ là ước của $3$
$\Rightarrow \sqrt{x}-2\in \left\{\pm 1; \pm 3\right\}$
$\Rightarrow x\in\left\{9; 1; 25\right\}$
Mà $x\neq 1$ nên $x\in\left\{9;25\right\}$